As práticas pedagógicas e o desenvolvimento dos conceitos não-cotidianos na criança pré-escolas - Barbosa, Eliza Maria [UNESP] (My University, 2012)
This article discusses non-daily concept formation in children talking about contributions from historical-cultural theory, highlighting school learning and teaching mediation as effective instruments on the development of these concepts. The goal is to reaffirm the understanding that it is by teaching activity that children acquire cultural concepts that are necessary to their humanization process. It also discusses the opposition established between psychogenic understanding on the formation of non-spontaneous concepts and the perspective in this historical-cultural theory, lines of development of daily concepts and not daily ones, and finally highlights the assumption that school educative practices are universal and necessary forms for this development.

O artigo trata da formação dos conceitos não-cotidianos nas crianças abordando as contribuições da teoria Histórico-Cultural, destacando as aprendizagens escolares e as mediações pedagógicas como instrumentos efetivos de desenvolvimento desses conceitos. O objetivo é reafirmar a compreensão de que é pela atividade de ensino que as crianças adquirem os conceitos culturais, necessários para o seu processo de humanização. Discute a oposição que se estabelece entre a compreensão Psicogenética sobre a formação dos conceitos não espontâneos2 e a perspectiva presente na teoria Histórico-Cultural, as linhas de desenvolvimento dos conceitos cotidianos e não cotidianos e por fim, destaca o pressuposto de que as práticas educativas escolares são formas universais e necessárias a esse desenvolvimento.
Pedagogical practices and development of nondaily concepts at pre-school child
Keywords: School learning; Non-daily concepts; Historical and Cultural Theory; Aprendizagem escolar; Conceitos não-cotidianos; Teoria Histórico-Cultural